An evaluation of the knowledge of the registered midwives managing hypertensive disorders at primary health care level in the Eastern Cape - Ngwekazi, Nompumelelo Lorraine (Stellenbosch : Stellenbosch University, 2013)
Thesis (MA)--Stellenbosch University, 2010.